PENGARUH TINGAT PENDIDIKAN TERHADAP PERNIKAHAN USIA DINI DI KECAMATAN PRAYA BARAT - Khairul Azmi; Mariawati Mariawati; Baiq Sitikamilatunnisak; Tamhadi Tamhadi (Prodi PAI STIT Sunan Giri Bima, 2023)
Early marriage or often referred to as underage marriage is a marriage that is carried out between a man and a woman who are not yet of the age specified by law. The purpose of this study is to determine the effect of the level of education on early marriage in West Praya District. The method used in this study is a quantitative descriptive method, because the problems discussed in this study are related to statistical figures and the results of this study will also involve descriptions, breakdowns, and descriptions of an ongoing problem which is described in percentage form. Data collection techniques through observation, documentation and interviews with the Head of the Office of Religious Affairs in West Praya Subdistrict regarding early marriage in 2022 and interviews with perpetrators of early marriage. he results showed that the level of education had an effect on the occurrence of early marriage in West Praya District, Central Lombok Regency in 2022. ased on the results of the study, the majority of graduates were married, namely those with primary school education.